KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN CERAH JAYA ABADI - Deddy Tantoroputro (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2017)
Cerah Jaya Abadi engages in health food and beverage industry. One of the company's products is Papione, which produces Papua red fruit cookies.The study aims to clarify the influence of product quality and service quality on Cerah Jaya Abadi’s customer satisfaction. This research is a quantitative descriptive research with interview as data collection method. Saturated sampling is used to select 64 research respondents. These respondents are consumers of Cerah Jaya Abadi who have made more than one purchase. Research data are collected using questionnaire, followed by interviews with five respondents selected using convenience sampling method. The three variables in this study are Product Quality (X1), Service Quality (X2), and Customer Satisfaction (Y). Multiple Linear Regression is used as analysis technique in this study. Research results suggest that product quality and service quality significantly influence Cerah Jaya Abadi's customer satisfaction.